Exploring the Concept of Ma'rifatullah as Preparation for Marriage: Thematic Study of Tafsir al-Misbah - Khairun Nisa, Jauharah; Alfani, Ilzam Hubby Dzikrillah (Universitas Ahmad Dahlan, 2025)
This research is motivated by the high divorce rate in Indonesia, which indicates a fragility in marital resilience. The root of the problem often lies in the daily interaction dynamics between partners with different characters and backgrounds. This article aims to explore the concept of ma’rifatullah (deep knowledge of Allah) as a fundamental spiritual provision for building household resilience and harmony. To achieve this objective, this study employs a qualitative method with a library research approach and applies thematic interpretation (tafsir maudu’i). The primary data source is Tafsir Al-Misbah by Muhammad Quraish Shihab, used to analyze QS. Az-Zāriyāt [51]: 56, QS. Al-Baqarah [2]: 2-3, QS. Ar-Rūm [30]: 21, and QS. Aṭ-Ṭalāq [65]: 2-3. This is supported by secondary sources such as relevant journals and books. The research findings conclude that ma’rifatullah offers a solid spiritual foundation by instilling the values of piety (taqwa), patience (sabr), gratitude (shukr), and trust in God (tawakkal). These values serve as a practical guide for couples in navigating conflict and household dynamics. Thus, the internalization of ma’rifatullah plays a crucial role as a shield against dissolution and as a bonding agent for realizing a family embodying tranquillity (sakinah), love (mawaddah), and mercy (rahmah).